Jahresbericht 2014 - (:unkn) unknown (Amt für Veröffentlichungen der Europäischen Union, 2015)
"Better links between education and training and the labour market was a main thread of the Greek and Italian EU Presidency programmes of 2014. This thread guided Cedefop’s work and demand for its expertise throughout the year. The new-look 2014 annual report presents a concise picture of Cedefop's activities as well as detailed information on the work of each department. It is packed with user-friendly charts and infographs showcasing the year's highlights." (Hrsg., BIBB-Doku)
Keywords: S 3.5.5.1 CEDEFOP; S 2.3 Berufsbildungspolitik; CEDEFOP; EU-Bildungspolitik; Berufsbildung; Weiterbildung; Qualifikationsbedarf; Analyse; Kommunikation; Kooperation